A Review of Mana and Manas Roga From Traditional Ayurvedic Literature - Kuldeep; Gandharve, Satish; Sood, Rajesh; Sharma, Sonia (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: This paper discusses the concept of health in Ayurveda, which is based on the balance of bio energies, digestive fire, body tissues, excretory functions, and emotional well-being. The triad of life, which consists of Sattva, Aatma, and Sharir, is crucial to achieve overall well being. The disturbance of the Doshas of Mana, Rajas and Tamas, can lead to Manas roga, which is a psychological disorder caused by an emotional imbalance. Methods: This paper reviews classical Ayurvedic texts to provide insights into the causes, symptoms, prevention, and management of Manas roga from an Ayurvedic perspective.Results: Ayurvedic texts describe several instances of Mana and Manas roga, providing a comprehensive understanding of their causes, symptoms, prevention, and management. Ayurveda emphasizes the importance of a balanced lifestyle, ethical conduct, and yoga practices in maintaining mental and emotional health. Conclusion: Ayurveda considers mental and emotional health to be as important as physical health, and the balance of mind and body is crucial for overall well-being. By understanding the causes, symptoms, prevention, and management of Manas roga from an Ayurvedic perspective, individuals can take proactive measures to maintain good mental and emotional health. This paper provides a valuable resource for healthcare professionals and individuals seeking to achieve balance and well-being in their lives.